PENGGUNAAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN KETERAMPILAN MENULIS BERITA DI SMP NEGERI 2 SAWIT BOYOLALI - Andriani, Rossy (Manajemen Pendidikan, 2019)
The lack of news writing skills of grade VIII student is caused by several factors including: students speak more often, so they do not focus on writing habits that cause students to be lazy. In this study the object of research in class VIII SMP N 2 SAWIT Boyolali consisted of 10 students. Data collected by several techniques such as observation and tests. Analysis of the data is a research procedure that is data in the form of written words. Data collection instruments used in the study are guidelines or observations and test. Audio visual results of observations and assesment about the use of media in news writing material have a change in direction for the better. In the first cycle using an audivisual media score reached 31 with a score of 60 included in the exellent category. From the written test results in cycle 1 the average score of 70 students with classical completeness of 46.6% and written test results in cycle 2 the average score of student was 83.9% with classical completeness of 93.3%. improvements obtained by students in earch cycle prove that the use of audio visual media on news text writing material can be said to be effective